Transforming Education: Advancing Diversity, Equity, Inclusion, and Belonging for Systemic Change - Brandon J Cheeks (Educational Considerations, 2025)
This paper examines how Diversity, Equity, Inclusion, and Belonging (DEIB) practices can help address educational inequalities, particularly those rooted in systemic racism. Drawing on Critical Race Theory (CRT), it argues that embedding DEIB into educational systems is essential for dismantling the barriers that perpetuate inequity. The paper highlights how DEIB practices, when applied systematically, can foster collaboration, challenge entrenched inequalities, and promote educational transformation. It calls on educators, policymakers, and scholars to adopt DEIB principles within school policies, curricula, and professional development to create more inclusive educational environments, ensuring all students—especially students of color—can achieve their full potential. This paper calls on educators, policymakers, and leaders to reframe current educational practices and prioritize DEIB in the pursuit of equity. This transformation requires addressing entrenched power structures and shifting from superficial diversity efforts to systemic reforms that ensure long-term, meaningful change. DEIB should be seen not as an "add-on" but as a central framework for reshaping educational practices, policies, and goals.
Keywords: Diversity; equity; inclusion; belonging; educational inequality; systemic racism; Critical Race Theory; educational transformation; systemic change; educational policy; educational reform; social justice in education; teacher professional development